IMPLEMENTASI PERATURAN WALI KOTA SAMARINDA NOMOR 51 TAHUN 2012 TENTANG KAWASAN TANPA ROKOK (KTR) PADA SEKOLAH MENENGAH PERTAMA (SMP) DI SAMARINDA - Rafika Febi Rivalda (Journal of Law ( Jurnal Ilmu Hukum ), 2020)
AbstractAs a follow-up, the Minister of Education issued the Republic of Indonesia Minister of Education Regulation No. 64 the Year 2015 concerning No-Smoking Areas in School Environments related to No-Smoking Areas (KTR). The non-smoking area aims to create a clean, healthy, and smoke-free school environment. Therefore, the prohibition of smoking in educational areas is one of the efforts to avoid the presence of minors who smoke. In addition to the students not smoking in the education area, this is also done so that the teachers give a good example to their students.The type of research the author uses is empirical juridical research, that is empirical juridical research, or so-called field research that examines applicable legal provisions and what happens in reality in society.The results of the study stated that the implementation of law enforcement areas without smoking in Samarinda City has not been effective. This is based on the results of a survey conducted by the Samarinda City Health Office that only 30% of the community complied while 70% of the community did not comply with the No Smoking Area. For the effectiveness of the No-Smoking Zone, a preventive effort is carried out, namely socialization, coordination, guidance, and provision of guidelines, as well as monitoring and evaluation and repressive efforts, namely by conducting spot checks and the imposition of sanctions for violators without smoking areas. The obstacles encountered by the government in law enforcement in the No Smoking Area in Samarinda City are affected by legal factors, factors of law enforcement officials, supporting facilities or facilities, community factors, and cultural factors.Keywords: Regions, Schools, Cigarettes